2020
DOI: 10.1111/1742-6723.13680
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 social restrictions on trauma presentations in South Australia

Abstract: Objective To review the impact of COVID‐19 social restrictions on trauma presentations in South Australia. Methods Retrospective database review. Results During the period of social restrictions, there was a reduction in presentations of trauma and major trauma by 17% and 33%, respectively. The reduction in presentation rates was due to a large decrease in those aged over 40, with an increase in presentations in those younger than 40. Review by mechanism and location of injury revealed a reduction in road trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 2 publications
6
40
0
Order By: Relevance
“…As expected, home‐related injuries formed the majority of plastic surgery emergency workload during the lockdown period at Peninsula Health. Similar findings have been reported in South Australia, where a 20% increase in injuries occurring at home was observed 21 . A surge in home‐related paediatric trauma have also been described in other centres during the pandemic 22 .…”
Section: Discussionsupporting
confidence: 85%
“…As expected, home‐related injuries formed the majority of plastic surgery emergency workload during the lockdown period at Peninsula Health. Similar findings have been reported in South Australia, where a 20% increase in injuries occurring at home was observed 21 . A surge in home‐related paediatric trauma have also been described in other centres during the pandemic 22 .…”
Section: Discussionsupporting
confidence: 85%
“…In contrast Harris et al . reported a 33% reduction in major trauma presentations compared to 7‐week period prior to lockdown 21 . The differences in part may be explained by the fact these two studies are from different Australian states with varying public health restrictions and different endemic levels of COVID‐19.…”
Section: Discussionmentioning
confidence: 93%
“…Since the onset of public health interventions to control the COVID‐19 pandemic there have been many reports outlining the effect of these interventions on general surgical trauma admissions from around the world 1,6–21 . Various methodologies have been employed with commonly short periods of time used and a time period before the interventions used as a comparator.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the World Health Organization reported that more than half of the countries surveyed had partially or completely disrupted services for the treatment or clinical management of hypertension, diabetes and diabetes-related complications, cancer, and cardiovascular emergencies [ 18 ]. A similar situation exists in Australia, where there have been marked reductions in a wide range of health services, including breast and prostate cancer screenings [ 19 , 20 ], pediatric orthopedic hospital services [ 21 ], trauma care in Emergency Departments [ 22 , 23 ], and initiation of cardiopulmonary resuscitation by Emergency Medical Services in public areas [ 24 ]. It is important to note that our findings encompass only the initial disruption caused by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 94%